Hubungan Daya Ledak Otot Tungkai Dengan Kemampuan Shootting Pemain Sepakbola SMAN 3 Kota Bengkulu - Hanif, Naufal; Ferdiansyah, Rahmad; Syaputra, Roni (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
Football is a team game where each football team consists of 11 players, where this game requires high collectivity to achieve maximum results. In the game of soccer, basic techniques are components that must be trained because they can foster instincts towards ball control. This basic technique training must also be done repeatedly to get maximum results. The relationship of leg muscle strength to the shooting ability of soccer players of SMA Negeri 3 Bengkulu is 86%. With the discovery of a significant relationship of leg muscle strength to the shooting ability of SMA Negeri 3 Bengkulu soccer players, leg muscle strength can be used as a tool to predict the shooting ability of soccer games. The agility test and dribbling ability obtained rtable of 0.343 because the correlation coefficient between rxy = 0.931> 0.343 and a contribution of 86%, which means that the contribution of leg muscle strength to the shooting ability of SMA Negeri 3 Bengkulu football players is significant and large.